Financial reforms and industrialisation: Evidence from Nigeria - Oludele E. Folarin (African Governance and Development Institute (AGDI), 2019)
Nigeria adopted the Structural Adjustment Programme (SAP) in 1986 after the crash in world oil price in the early 1980s. Financial reforms are part of the reforms implemented during the SAP. Since, industrialisation is seen as an engine of growth, we conduct an empirical assessment of the effects of financial sector reforms on industrialisation in Nigeria using an annual time series data over 1981 - 2015. Using an autoregressive distributed lag (ARDL) model, our findings show that financial reforms have a positive and significant impact on industrialisation.
Keywords: C32; E44; O14; O55; 330; Financial reforms; Financial repression; Industrialisation; ARDL bounds test